SOCIO-CULTURAL NETWORK AND COMMUNICATION BETWEEN MISHING AND ADI COMMUNITIES IN BORDER AREAS OF ASSAM AND ARUNACHAL PRADESH - Koijam, Sunil; Doley, Pranjit (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Borders play a fundamental role in defining state territories, shaping geopolitical dynamics, and influencing interactions between borderland communities. Anthropologists view border regions as crucial sites for exploring sociocultural processes emerging from state territorialization, local social organization, and individual agency. These areas reveal how people encounter, reinforce, and subvert political boundaries in everyday practices. Border existence fosters activities like small-scale trade, tourism, and cultural exchanges, facilitating daily interactions and symbolic identity constructions. Despite different traditions and practices separated by borders, these interactions shape ways of living and thinking. Numerous studies on India's social and cultural networks focus on single linguistic zones, neglecting cross-border socio-cultural communication. Assam and Arunachal Pradesh share an 804.10 sq. km border, presenting a unique context where the border is a site of social contact, composite cultures, and co-existence. This study examines inter-ethnic communication and cultural exchange between the Mishing and Adi communities along the Assam-Arunachal Pradesh border. It investigates cross-border interactions, providing insights into socio-cultural networks that operate differently within single areas. This research aims to illuminate how these borderland communities navigate and negotiate cultural identities and social relations amidst complex border dynamics.